Energy and environmental assessment of a traditional durum-wheat bread. (10th January 2018) - Ingrao, Carlo; Licciardello, Fabio; Pecorino, Biagio; Muratore, Giuseppe; Zerbo, Antonio; Messineo, Antonio
Abstract: This study was designed and developed to investigate the bread sector, by addressing the environmental issues associated with the supply chain of ' Pagnotta del Dittaino', a Protected Designation of Origin (PDO) durum wheat bread produced in the central-east area of Sicily. In particular, the study discusses the application of Life Cycle Assessment (LCA) to highlight the most significant and representative environmental impacts for this bread production system. Cumulative Energy Demand (CED) and Carbon Footprint (CF) were also estimated to address the usage of primary-energy sources and the emissions of GreenHouse Gases (GHGs). Cultivation is the system hotspot, mostly because of the production of urea and diammonium phosphate, and of the agricultural activities. Significant contributions arise from ammonia volatilisation and nitrous oxide emission due to mineral fertilisation, affecting 'Human health' and 'Climate Change' . ' Resources' were impacted by the non-renewable energy use (natural gas and crude oil) which, in turn, is due to the production and transport of fertilisers and to the agricultural activities. Additionally, the CED-analysis highlighted the important contribution made by the use of biomass energy, as a consequence of the energy sequestered by the plant during growth. CO2 resulted to be the most relevant and representative GHG in this food system. The study contributes to the subject knowledge and literature, and can be of interest for researchers, LCA practitioners, farmers and producers, policy makers and other stakeholders, and could support the implementation of environmental labels. Highlights: The paper addresses the environmental issues of a durum wheat bread. Primary and secondary data were inventoried and used for the LCA. Major environmental impacts were related with the cultivation phase. CO2 is the most representative and relevant greenhouse gas based on GWP100 . Non-renewable energy is one of the most significant impact categories.